The effect of starch and starch-bioactive glass composite microparticles on the adhesion and expression of the osteoblastic phenotype of a bone cell line - Silva, G. A. (2007)
There is a clear need for the development of microparticles that can be used simultaneously as carriers of stem/progenitor cells and as release systems for bioactive agents, such as growth factors or differentiation agents. In addition, when thinking on bone-tissueengineering applications, it would be very useful if these microparticles are biodegradable and could be made to be bioactive. Microparticles with all those characteristics could be cultured together with adherent cells in appropriate bioreactors to form in vitro constructs that can then be used in tissue-engineering therapies. In this work, we have characterized the response of MC3T3-E1 pre-osteoblast cells to starch-based microparticles. We evaluated the adhesion, proliferation, expression of osteoblastic markers and mineralization of cells cultured at their surface. The results clearly show that MC3T3-E1 pre-osteoblast cells adhere to the surface of both polymeric and composite starch-based microparticles and express the typical osteoblastic marker genes. Furthermore, the cells were found to mineralize the extracellular matrix (ECM) during the culture period. The obtained results indicate that starch-based microparticles, known already to be biodegradable, bioactive and able to be used as carriers for controlled release applications, can simultaneously be used as carriers for cells. Consequently, they can be used as templates for forming hybrid constructs aiming to be applied in bone-tissue-engineering applications.